Estimation of Demand Elasticity for Food Commodities in Java Island - Devi, Laksmi Yustika; Purnomosidi, R Y Kun Haribowo (Universitas Negeri Semarang, 2019)
Food availability is a development priority. Along with the increasing population growth, safe and nutritious food is rising. Analysis of food consumption patterns is needed to estimate the demand for agricultural products. This study attempts to analyze consumption patterns and food demand for several commodities in Java by using the 2010-2017 National Socio-Economic Survey data collected by Statistics Indonesia. Results of this study are: 1) the demand for quantity of rice is not elastic to income; (2) the demand for quantity of fresh fish, shrimp, beef and chicken meat is elastic to income; (3) the budget elasticity of fresh fish, shrimp, beef and chicken meat is also large, which means that households will increase the quantity and budget for these three commodities; (4) quantity and budget elasticity in rural are generally greater than urban; (5) in urban areas, budget elasticity is greater than quantity elasticity for all commodities, while in rural, budget elasticity is smaller than quantity elasticity, except for sugar, fresh fish and shrimp; (6) there has been a shift in the proportion of food expenditure on Java, e.g. the proportion of expenditures for grains decreases and the proportion of expenditures for prepared food and beverages increases.